Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.3 - Derivatives of Trigonometric Functions - 3.3 Exercises - Page 196: 10



Work Step by Step

$y=\sin\theta\cos\theta$ Differentiate using the product rule: $y'=(\sin\theta)(\cos\theta)'+(\cos\theta)(\sin\theta)'=...$ $...=(\sin\theta)(-\sin\theta)+(\cos\theta)(cos\theta)=-\sin^{2}\theta+\cos^{2}\theta=\cos^{2}\theta-\sin^{2}\theta$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.